PERANCANGAN GEDUNG KREATIF DAN PEMBERDAYAAN REMAJA DI TANGERANG SELATAN DENGAN ARSITEKTUR KONTEMPORER - Setiawan, Rahmad Dodie; Kurniawan, Dody; Kurniasih, Sri (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
Abstract Based on the journal of family As the Center of Education In the Development of Society written by C.Asri Budiningsih say that education in Indonesia is practically just pay attention and analyze the problems of formal education at the school. The design of the Building Creative and Empowerment of youth this is the place that becomes the center of activities of the teenagers who are in the inside in the form of training sites,art galleries & recreational facilities. A creative activity intended as a means of youth empowerment-based non-formal education to improve human resources active, intelligent and can develop the potential of youth in the region.. The presence of this Creative Centre aims to accommodate the youth in South Tangerang to activities in the facility to take advantage of the free time with things that are positive